ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT ASTRA INTERNATIONAL, Tbk - Fajarwati, Fajarwati; Muriko, Nofriadi Muriko (Universitas Muhammadiyah Magelang, 2004)
Service quality is a final result of comparison beween service hoped by the costumers with their perseption to actual service performance. This research examines the influence of tangible, reability, responsiveness, assurance, and emphaty variables to costumer satisfaction of PT ASTRA INTERNATIONAL at Magelang Street km 7.2 Yogyakarta. The result of this research show that those five service quality variables: tangible, reability, responsiveness, assurance, and emphaty, had influence to customer satisfaction. Partially variables that significantly have influence om costumer satisfaction are tangible, reability, responsiveness, assurance, and emphaty, where reability did not have influence significanly on costumers satisfaction. From those five service quality variables, he most dominant variable on costumers satisfaction is responsiveness variable.